Magnus Chase and the Hammer of Thor - Riordan, Rick (London Puffin Books, 2016)
The second book in this number one, bestselling series from the creator of Percy Jackson.Thor's hammer is missing againvery high.
Keywords: Children's stories -- Homeless children -- Mythology, Norse